Expression of tandem gene duplicates is often greater than twofold - Loehlin, David W. (Proc Natl Acad Sci U S A, 2016)
Tandem gene duplication is an important mutational process in evolutionary adaptation and human disease. Hypothetically, two tandem gene copies should produce twice the output of a single gene, but this expectation has not been rigorously investigated. Here, we show that tandem duplication often results in more than double the gene activity. A naturally occurring tandem duplication of the Alcohol dehydrogenase (Adh) gene exhibits 2.6-fold greater expression than the single-copy gene in transgenic Drosophila. This tandem duplication also exhibits greater activity than two copies of the gene in trans, demonstrating that it is the tandem arrangement and not copy number that is the cause of overactivity. We also show that tandem duplication of an unrelated synthetic reporter gene is overactive (2.3- to 5.1-fold) at all sites in the genome that we tested, suggesting that overactivity could be a general property of tandem gene duplicates. Overactivity occurs at the level of RNA transcription, and therefore tandem duplicate overactivity appears to be a previously unidentified form of position effect. The increment of surplus gene expression observed is comparable to many regulatory mutations fixed in nature and, if typical of other genomes, would shape the fate of tandem duplicates in evolution.